New data on the stratigraphy and chronology of the prehistoric site of Prazo (Freixo de Numão) - Monteiro-Rodrigues, Sérgio (2004)
The Prazo archaeological site is located near Freixo de Numão (Vila Nova de Foz Côa, north-eastern Portugal). The site, discovered in the early 80s, initially revealed a significant historical record, having been a Roman villawhose occupation continued through part of the Middle Ages. In 1996, fieldwork there uncovered Neolithic layers. They were excavated from 1997 to 2001, revealing also the existence of a pre-Neolithic occupation. This paper presents the geoarchaeology and chronology of the prehistoric succession of Prazo, which is arranged as follows: an upper Pleistocene complex formed of slope waste sediments, featuring upper Palaeolithic finds and structures; an early to mid Holocene succession, also composed from slope waste deposits, containing Epipalaeolithic/Mesolithic and Early Neolithic archaeological assemblages and features; and an upper Holocene complex, corresponding to occupations in the Roman and Middle Ages. The available data deriving from the geoarchaeological survey at the site and from an extensive range of radiocarbon dates are presented as part of a preliminary discussion of the environmental evolution and the settlement strategies at the site.